(untitled) (Journal of Entrepreneurship and Business, 2021)
The study employed the methodological approach of reflexive ethnography to analyse management accounting in microfinance. Research Objective: The study aims to present an illustration of reflexive ethnography and its application in investigating management accounting in an informal setting, specifically a rural village in Bangladesh. Method: The study used a reflexivity lens that presents a detailed account of the author’s personal doctoral journey in gaining access to and exploring the field, analysing field data, and overcoming challenges. Empirical Result: The study highlights how to overcome the barrier of ‘functional stupidity’ while examining (management) accounting, governance, and related issues in microfinance. Practical Implications: The contributions include enhancing the accounting and development literature which are dominated by functional paradigm. Moreover, alternative approaches were proposed, such as reflexive ethnography to recognise a more mundane form of management accounting and governance